Absence of lower genital tract lesions among women of reproductive age infected with Schistosoma mansoni: A cross-sectional study using a colposcope in Western Kenya. - Huldah C Sang; Pauline N M Mwinzi; Maurice R Odiere; Isaac Onkanga; Fredrick Rawago; Pavitra Pillay; Eyrun Floerecke Kjetland (PLOS Neglected Tropical Diseases, 2022)
Background Female genital schistosomiasis (FGS) constitutes four different lesions known to be caused by Schistosoma haematobium ova deposited in the genital tract. Schistosoma mansoni ova may also be found in the genital tract. However, it is not known if S. mansoni causes lower genital tract lesions characteristic of FGS. Methodology This study was conducted in 8 villages along the shores of Lake Victoria, western Kenya. Stool and urine samples, collected from women of reproductive age on three consecutive days, were analysed for S. mansoni and S. haematobium infection. S. mansoni positive and S. haematobium negative willing participants, aged 18-50 years were invited to answer a questionnaire (demographics, symptoms), undergo a gynaecological examination and cytology specimen collection by an FGS expert. Principal findings Gynaecologic investigations were conducted in 147 S. mansoni-positive women who had a mean infection intensity of 253.3 epg (95% CI: 194.8-311.9 epg). Nearly 90% of them used Lake Victoria as their main water source. None were found to have cervicovaginal grainy sandy patches or rubbery papules. Homogenous yellow patches were found in 12/147 (8.2%) women. Women with homogenous yellow patches were significantly older (47 years) than the rest (34 years, p = 0.001). No association was found between intensity of S. mansoni infection and homogenous yellow patches (p = 0.70) or abnormal blood vessels (p = 0.14). S. mansoni infection intensity was not associated with genital itch, bloody or malodorous vaginal discharge. Conclusion S. mansoni infection was neither associated with lower genital tract lesions nor symptoms typically found in women with FGS.